Peran Masyarakat dalam Pencegahan Covid-19 Serta Efektifitas Pelatihan Bagi Masyarakat Desa - Sutikno, Bambang; Marsidi, Marsidi; Rindawati, Septi; Ditasman, Ditasman; Romdana, Romdana (Jurnal Semarak Mengabdi, 2022)
Most of the people in the Sebakul village don't care about the dangers of covid 19 that are hitting their village. In various generations, people are rarely seen wearing masks. This is a special note for the government in paying attention to its people. For example, what is happening now, where weddings are very vulnerable to the circulation of this virus? And as if he doesn't care about his health, it is necessary to take action or research that the level of knowledge must be wider. In order to comply with the regulations that should be from the central government, it is safe for the community. it is necessary to carry out creative programs that can take community sympathizers to their awareness of the dangers of the spread of Covid 19, for example by conducting awareness training on the spread of Covid 19, conducting counseling to villages. Automatically it will be more effective in inhibiting the spread of the Covid 19 virus.